Ultra-thin conformal coatings for electrostatic dissipation in semiconductor process tools.
By using conductive dissipation coating on the end effector and contact plate of the robot arm during the manufacturing process of electronic equipment, the problem of plate defects caused by electrostatic charge is solved, and the stability and efficiency of the manufacturing process is achieved.
Patent Information
- Application Number
- JP2022518258
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-02
- Filing Date
- 2020-09-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-09-28
AI Technical Summary
During the electronics manufacturing process, fast-moving robots may generate electrostatic charges when transporting silicon matrix boards, resulting in plate defects. The prior art is difficult to effectively solve the problem of plate defects caused by electrostatic charge.
Using an electrodissipative coating, a layer of conductivity dissipative material is deposited on the end effector of the robot arm and the contact plate. The coating provides a charge dissipation path from the surface to the ground, preventing the accumulation of electrostatic charges.
Effectively prevent the accumulation of electrostatic charge on the end effector and contact plate of the robot arm, reduce the occurrence of plate surface defects, and improve the stability and efficiency of the electronic equipment manufacturing process.
Smart Images

Figure 0007662619000003 
Figure 0007662619000004 
Figure 0007662619000005
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE Embodiments of the present disclosure relate generally to coated semiconductor process tools (such as apparatus for transporting objects within a processing system), electrically dissipative coatings, and methods for depositing such coatings. In particular embodiments, the present disclosure relates to an end effector of a robotic arm coated with an electrically dissipative material. [Background technology]
[0002] In the manufacture of electronic devices, substrates (e.g., silicon-containing wafers, silicon-containing plates) may be moved within manufacturing facilities and manufacturing equipment tools by robots. The robots may include a robot arm having one or more end effectors coupled thereto that can contact and support the substrate during such transport. The end effectors include contact pads thereon that provide elevated contact surfaces on which the substrate is supported. Summary of the Invention
[0003] In certain embodiments, the disclosure may be directed to a coated chamber component, including a chamber component and a coating deposited on a surface of the chamber component. In certain embodiments, the coating may include an electrically dissipative material. The electrically dissipative material may provide a dissipative path from the coating to ground. The coating may be uniform, conformal, and nonporous. The coating may have a thickness ranging from about 10 nm to about 900 nm, and a surface area of about 1×10 5 Ω / sq.~approx. 1×10 11 It may have an electrical surface / sheet resistance in the range of Ω / sq.
[0004] In certain embodiments, the disclosure may be directed to a method including depositing a coating on a surface of a chamber component using an atomic layer deposition (ALD) process, a chemical vapor deposition (CVD) process, a plasma enhanced atomic layer deposition (PEALD) process, a metalorganic chemical vapor deposition (MOCVD), or a molecular beam epitaxy (MBE) process. The coating may include an electrically dissipative material. The electrically dissipative material may provide a dissipative path from the coating to ground. The coating may be uniform, conformal, and nonporous, with a thickness ranging from about 10 nm to about 900 nm, and a surface area of about 1×10 5 Ω / sq.~approx. 1×10 11 It may have an electrical surface / sheet resistance in the range of Ω / sq.
[0005] In certain embodiments, the disclosure may be directed to an electrically dissipative coating that includes an electrically dissipative material. The coating may be uniform, conformal, and nonporous, with a thickness ranging from about 10 nm to about 900 nm, and a surface area of about 1×10 5 Ω / sq.~approx. 1×10 11 It may have an electrical surface / sheet resistance in the range of Ω / sq.
[0006] In certain embodiments, the disclosure may be directed to an end effector for a robotic arm. The end effector may include an end effector body and a coating deposited on a surface of the end effector body. The coating may include an electrically dissipative material. The electrically dissipative material may provide a dissipative path from the coating to ground. The coating may be uniform, conformal, and nonporous. The coating may have a thickness in the range of about 10 nm to about 900 nm. The coating may have a thickness in the range of about 1×10 5 Ω / sq.~approx. 1×10 11 It may have an electrical surface / sheet resistance in the range of Ω / sq.
[0007] In certain embodiments, this disclosure may be directed to a method. The method may include depositing a coating on a surface of an end effector for a robotic arm using an atomic layer deposition (ALD) process, a chemical vapor deposition (CVD) process, a plasma enhanced atomic layer deposition (PEALD) process, a metal organic chemical vapor deposition (MOCVD), or a molecular beam epitaxy (MBE) process. The coating may include an electrically dissipative material. The electrically dissipative material may provide a dissipative path from the coating to ground. The coating may be uniform, conformal, and nonporous. The coating may have a thickness in the range of about 10 nm to about 900 nm. The coating may have a thickness in the range of about 1×10 5 Ω / sq.~approx. 1x10 11 It may have an electrical surface / sheet resistance in the range of Ω / sq.
[0008] In certain embodiments, the disclosure may be directed to a substrate processing system. The substrate processing system may include a chamber, a robot disposed within the chamber, and a robot arm connected to the robot. The robot arm may include an end effector body, a replaceable contact pad, and a coating. The replaceable contact pad may be disposed on the end effector body. The replaceable contact pad may include a contact pad head having a contact surface configured to contact a substrate, and a shaft coupled to the contact pad head and received within an aperture formed in the body of the end effector and extending into a recess. The coating may be deposited on a surface of the end effector body and a contact surface of the contact pad head. The coating may include an electrically dissipative material. The electrically dissipative material may provide a dissipative path from the coating to ground. The coating may be uniform and conformal.
[0009] The present disclosure is illustrated by way of example, and not by way of limitation, in the figures of the accompanying drawings, in which like references represent similar elements. It should be noted that in this disclosure, different references to "an" or "one" embodiment are not necessarily to the same embodiment, and such references denote at least one embodiment. [Brief description of the drawings]
[0010] [Figure 1] 1 is a perspective view of an example of an end effector including one or more contact pads provided in accordance with an embodiment of the present disclosure. FIG. [Diagram 2] FIG. 13 is a side view of a coated end effector body according to an embodiment of the present disclosure. [Diagram 3] 2A is a partial cross-sectional view along section 2A-2A of FIG. 1 of a portion of an end effector including a replaceable contact pad, according to an embodiment of the present disclosure. [Figure 4] FIG. 1 illustrates an atomic layer deposition process that may be used to coat an end effector body for a robot arm or another chamber part, according to an embodiment of the present disclosure. [Diagram 5] FIG. 1 illustrates an exemplary chamber for a chemical vapor deposition process that may be used to coat an end effector body for a robot arm or another chamber part in accordance with an embodiment of the present disclosure. [Figure 6] FIG. 1 is a top schematic view of an electronic device manufacturing apparatus including a transfer robot having an end effector including replaceable contact pads that may be co-coated in accordance with one or more embodiments of the present disclosure. [Figure 7A] FIG. 1 illustrates an EDS line scan of a coating according to an embodiment of the present disclosure. [Figure 7B] FIG. 7B shows a TEM image at 50 nm scale of the coating depicted in FIG. 7A. [Figure 8] FIG. 1 illustrates electrical surface / sheet resistance of a coating as a function of air pressure, according to one embodiment. [Figure 9A] 1 shows an image of the front surface of an exemplary end effector coated with a coating according to one embodiment. The sheet resistance values measured at each of the identified locations are summarized in Table 1. [Figure 9B]1 shows an image of the underside of an exemplary end effector coated with a coating according to one embodiment. The sheet resistance values measured at each of the identified locations are summarized in Table 1. [Figure 10A] 1 shows an image of the front surface of an exemplary bulk-doped ceramic end effector. The sheet resistance values measured at each of the identified locations are summarized in Table 2. [Figure 10B] 1 shows an image of the backside of an exemplary bulk-doped ceramic end effector. The sheet resistance values measured at each of the identified locations are summarized in Table 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the manufacturing process of electronic devices, a substrate (e.g., a silicon wafer, a silicon-containing plate, etc.) configured to produce electronic components (e.g., an electronic chip or electronic subcomponents thereof) is moved through multiple manufacturing steps, often by using one or more robots. The robot includes an end effector that supports the substrate during such movements. Moving the substrate very quickly can increase throughput and reduce manufacturing costs of the electronic components produced.
[0012] However, the fast motion of the robot in transporting the substrate may also generate electrically charged particles that may collect on surfaces, which may lead to substrate defects. Such substrate defects may be minimized by coating surfaces prone to charging (such as the end effector of the robot arm) with an electrically dissipative coating. The electrically dissipative coating may help bleed off the charge from the surface, allowing the particles to be freed from van der Waals forces and redispersed. The electrically dissipative coating may support electrostatic discharge and avoid arcing and other sudden conductive events between the charged chamber component surfaces (e.g., the charged end effector body) and / or the wafer thereon and other system components.
[0013] This disclosure encompasses various embodiments related to electrically dissipative coatings, methods of depositing such electrically dissipative coatings, chamber parts coated with electrically dissipative coatings, end effector bodies coated with electrically dissipative coatings, and substrate processing systems utilizing parts (e.g., chamber parts and / or substrate transport parts, such as end effectors) coated with such electrically dissipative coatings. In some embodiments, the electrically dissipative coating is also a plasma resistant coating.
[0014] The coating processes described herein can be advantageous and cost-effective because they can utilize bare chamber parts (such as end effector bodies) that are more readily available, face fewer manufacturing and yield issues, have short lead times, etc. Furthermore, multiple chamber parts (such as end effector bodies) may be coated simultaneously (e.g., by inserting multiple end effector bodies into an ALD, CVD, PEALD, MOCVD, or MBE deposition chamber). The resulting coatings can also be more uniform, more conformal, less porous, stronger, maintain their integrity longer (even under extreme conditions such as vacuum, thermal shock, thermal cycling), and have a narrower distribution of electrical surface / sheet resistance compared to chamber parts produced by other processes (such as bulk ceramic doping processes and slurry-based coating processes).
[0015] In an exemplary embodiment, the disclosure may be directed to a component for transporting a substrate coated with a coating having specific properties. In one embodiment, the component for transporting a substrate may be an end effector for a robotic arm. The coating may have an electrically dissipative property and may include an electrically dissipative material to provide a dissipative path from the coating to ground. The coating may be uniform, conformal, and nonporous. The coating may have a thickness in the range of about 10 nm to about 900 nm (e.g., about 20 nm to about 500 nm). The coating may have a thickness in the range of about 1×10 5 Ω / sq.~approx. 1×10 11 It may have an electrical surface / sheet resistance in the range of Ω / sq.
[0016] The body of the component for carrying the substrate may include an insulator or conductor, such as, but not limited to, ceramic, conductive material (such as metal), polymer, quartz, etc. In one embodiment, the body of the component for carrying the substrate may include a material suitable for high temperature processes, such as quartz. Quartz may be suitable for high temperature processes due to its transparency, which allows radiation to pass while minimizing thermal effects on the substrate being carried. The coating deposited on the component may retain some of the properties of the material of the underlying component. For example, the coating may retain the transparency of the underlying quartz component to maintain minimal thermal effects on the substrate. In certain embodiments, the coating deposited on the component may have certain properties that are independent of the material of the underlying component. For example, the resistive performance of the coating may be independent of the underlying component.
[0017] The coating may be a bilayer stack or a stack of multiple alternating layers. The coating may comprise a variety of materials and may be selected based on the target properties of the final coating (e.g., electrical dissipation properties, transparency, thermal conductivity, corrosion resistance, hardness, thermal shock resistance, thermal cycling resistance, vacuum resistance, scratch adhesion, wear rate, purity, roughness, conformality, etc.), among other factors. In certain embodiments, the coating may comprise a stack of alternating layers comprising a first material and a second material. The thickness ratio of the thickness of each layer comprising a first material to the thickness of each layer comprising a second material may range from about 50:1 to about 1:50. In one embodiment, the bilayer stack or the stack of alternating layers may comprise one or more of alumina and titania. The thickness ratio of the thickness of each alumina layer to the thickness of each titania layer may range from about 10:1 to about 1:10.
[0018] In certain embodiments, the component for transporting the substrate being coated may be an end effector. The end effector body may include replaceable contact pads thereon to reduce and / or eliminate slipping of the substrate from the surface of the end effector during transport. In an embodiment, the replaceable contact pads, along with the end effector, may be coated with any of the coatings described herein and using any of the coating methods described herein. Alternatively or additionally, the replaceable contact pads may be composed of an electrically dissipative material.
[0019] The coatings described herein may be deposited by atomic layer deposition (ALD) processes, by chemical vapor deposition (CVD) processes, by plasma enhanced atomic layer deposition (PEALD) processes, by metalorganic chemical vapor deposition (MOCVD) processes, by molecular beam epitaxy (MBE) processes, and other similar chemical precursor deposition processes. Coatings including two or more layers and / or two or more metals may be deposited through sequential deposition, through co-deposition, or through co-administration of precursors.
[0020] ALD (and optionally CVD, PEALD, MOCVD and / or MBE) may be the preferred deposition method in this disclosure due to its ability to uniformly and conformally coat parts with complex three-dimensional features, holes, large aspect ratios, etc. Additionally, using these coating processes, multiple bare, uncoated parts (e.g., end effectors) (e.g., bare bulk alumina not doped with titania) may be placed in a deposition chamber and coated simultaneously. Among other factors, inexpensive starting materials, the ability to coat multiple chamber parts simultaneously, and the flexibility and ability to optimize the coating process provide a more cost-effective process and, ultimately, more affordable coated parts.
[0021] As used herein, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, a reference to "a wafer" includes a single wafer as well as two or more wafers taken together, a reference to "metal" includes a single metal as well as two or more metals taken together, etc.
[0022] As used herein, the term "about" in connection with a measured quantity refers to normal variations in the measured quantity as would be expected by one of ordinary skill in the art when making the measurement and using a level of care commensurate with the purpose of the measurement and the precision of the measuring device. In certain embodiments, the term "about" includes the recited figure ±10%, such that "about 10" includes 9 to 11.
[0023] The description of ranges of values herein is merely intended to serve as a shorthand way of referring individually to each separate value contained in the range, and each separate value is incorporated into the specification as if it were individually described herein, unless otherwise indicated herein. All methods described herein can be performed in any suitable order, unless otherwise indicated herein or clearly contradicted by context. The use of any and all examples or exemplary language (e.g., "etc.") provided herein is intended merely to facilitate the description of certain materials and methods, and is not intended to limit the scope. No language in this specification should be construed as indicating that any unclaimed element is essential to the practice of the disclosed materials and methods.
[0024] As used herein, the term "plasma resistant" means resistant to one or more types of plasma, as well as resistant to the chemicals and radicals associated with one or more types of plasma.
[0025] Certain embodiments are discussed herein with reference to end effectors coated with an electrically dissipative coating. However, it should be understood that the electrically dissipative coatings described in the embodiments herein may also be used to coat other components, such as processing chambers, transfer chambers, factory interface chambers, load locks, load ports, slit valves, and the like. Thus, the electrically dissipative coatings described herein may coat any component of an electronic device processing tool or system. Some examples of such components include substrate support assemblies, electrostatic chucks, gas distribution plates, lids, nozzles, liners, rings (e.g., process kit rings or single rings), bases, showerheads, gas lines, liner kits, shields, plasma screens, flow equalizers, cooling bases, chamber viewports, chamber lids, and the like.
[0026] FIG. 1 illustrates a first exemplary embodiment of a chamber component that can be coated with an electrically dissipative coating as described herein. In FIG. 1, the exemplary chamber component is an end effector 100 configured to support a substrate 101 (a portion of which is shown in dashed lines). The end effector 100 can be made of an end effector body 102 having a top surface 102T (FIG. 2) and a bottom surface 102B. The top surface 102T can include a planar surface including three spot surfaces elevated above an underlying planar surface 102PS of the end effector body 102. The end effector body 102 can be configured to be coupled or interconnected at an inner end 104I to a robot component such as a robot arm (e.g., see FIG. 6, robot wrist 653). The coupling can involve fasteners (not shown) received through bores 105 to couple the end effector 100 to the robot arm (e.g., wrist 653). The connection may be made directly to the wrist member 653 or may be made through an intermediate component such as a mounting plate 654 (FIG. 6) to reduce cracking of the end effector 100 if the end effector 100 is made from a ceramic or glass material.
[0027] The outer end 104O of the end effector body 102 can include a first fork 107A and a second fork 107B, each of which can be configured to receive and support a contact pad 108 thereon. In some embodiments, the contact pads 108 are constructed from or coated with an electrically dissipative material. The contact pads 108 on the outer end 104O and a third contact pad 108 proximate the inner end 104I can provide a stable three-point contact for supporting the substrate 101 thereon (only a portion of the substrate 101 is shown in FIGS. 1 and 2). The substrate 101 can be supported on the contact pads 108 of the end effector 100 between an inner shelf 109I, which can be an arcuate step of approximately the same radius as the substrate 101, and an outer shelf 109O. The spacing between the respective inner and outer shelves 109I, 109O can be slightly larger (e.g., a few mm) than the substrate 101, dimension 111 can be 300 mm in diameter or 450 mm in diameter or a diameter slightly larger than other dimensions of the substrate 101, etc. Other configurations of the end effector body 102 than those shown can be used. The end effector 102 and / or contact pads 108 may be coated with an electrically dissipative coating in embodiments.
[0028] FIG. 2 is a side view of an exemplary end effector body 102 depicting a coating 200 deposited on the bottom surface 102B, top surface 102T, inner shelf 109I, outer shelf 109O, and top surface 102T. The dimensions of the end effector body 102 and the coating 200 may not be to scale and are depicted in FIG. 2 for illustrative purposes only. Contact pads 108 are not depicted in FIG. 2. Although the coating 200 is described herein as being deposited on the top surface (102T) of the end effector body 102, the coating 200 may also be deposited on the top surfaces of other chamber components, even if not explicitly described herein. Exemplary chamber components that may be coated with the electrically dissipative coating 200 may include a transfer chamber, a factory interface chamber, a load lock, a load port, a slit valve, and the like.
[0029] The end effector body 102 can be manufactured from a rigid material. In some embodiments, the end effector body 102 can be made from a stable, lightweight material that reduces deformation of the end effector under various chamber processing conditions, including pressure and temperature. Suitable, non-limiting materials for the end effector body 102 include insulating or conductive materials, such as, but not limited to, polymers, glass, quartz, ceramics, conductive materials (such as metallic materials), and the like.
[0030] For example, ceramics such as bulk alumina can be used. In some embodiments, suitable ceramics can be semiconductive to facilitate discharge of electrostatic charges that may build up on the substrate. Other semiconductive ceramic materials include, for example, alumina-SiC composites, SiC, silicon nitride, boron nitride, and boron. In certain embodiments, the coating 200 disclosed herein contributes to the semiconductive nature of the coated end effector body (or any coated chamber part). The semiconductive nature can avoid high conductance that may result in arcing between the coated chamber part (e.g., end effector) and other system parts. Such semiconductive nature can also be achieved by the coating 200 as described in more detail below.
[0031] Optionally, the end effector body 102 may include a conductive material such as a metal. Exemplary suitable conductive materials may include, but are not limited to, stainless steel, aluminum, nickel, copper, chromium, cobalt, molybdenum, ruthenium, tungsten, or platinum. Other suitable metals or alloys (e.g., aluminum alloy Al6061) may also be used. A conductive end effector body (or another conductive chamber part) may also be coated with a coating 200 to create a coated end effector body (or another coated chamber part) with electrically dissipative properties, which may support electrostatic discharge and avoid arcing and sudden conductive events between the end effector (or other chamber part) and / or the wafer and / or other system parts thereon.
[0032] The term "semiconductive" as used herein is meant to include bulk materials of a particular component that exhibit semiconductive electrical properties, as well as conductive or nonconductive bulk materials that are considered semiconductive due to, for example, a coating of semiconductive material or other semiconductive electrical pathways, such as wires, layers, ribbons, lines, or other electrical channels, disposed thereon or within them. Similarly, the term "conductive" as used herein is meant to include conductive bulk materials, or semiconductive or nonconductive materials that are considered conductive due to a conductive coating or conductive electrical pathways formed in or upon them.
[0033] In some embodiments, the end effector 100 can be used at temperatures between 150° C. and 650° C. In high temperature thermal processes, there can be significant heat transfer between the end effector and the wafer in close proximity. The thermal shock associated with heat transfer from an alumina end effector to the wafer can destroy the wafer. In contrast, the use of a transparent end effector, such as an end effector comprising quartz, does not impart such a dramatic thermal shock. The reduced thermal shock seen with quartz end effectors is believed to be due to quartz not being as thermally conductive as ceramics (such as alumina) and quartz being transparent (compared to opaque ceramic materials such as alumina) and therefore allowing radiation to pass through.
[0034] In certain embodiments, quartz may be used as a material of construction for end effectors used to transport substrates for thermal processing at high temperatures because quartz casts minimal thermal shadows (in other words, quartz has minimal thermal effects on wafers). Similarly, quartz may be used as a material of construction for other chamber components that benefit from its minimal thermal effects. In such embodiments, the coating may be transparent to preserve the advantageous properties of the quartz end effector, or any other quartz chamber components.
[0035] In certain aspects, it may be advantageous for the coating to maintain similar properties (e.g., transparency) to those of the material of the underlying component construction, while in other aspects, it may be advantageous for the coating to be independent of certain properties (e.g., resistance performance) from the material of the underlying component construction.
[0036] The rapid movement of the robot may generate particles when transporting the substrate. Electrostatic charges and the affinity of particles to collect on charged surfaces (e.g., the charged surface of the end effector body coupled to the robot arm) are believed to be one of the contributors to substrate defects. It is believed that coating the surface of the end effector body (or another chamber part exhibiting a similar phenomenon) with an electrically dissipative material such as the coating 200 may allow the charge to be discharged from the surface of the end effector body (or other chamber part). This allows the particles to be freed from van der Waals forces and redispersed. In other words, the electrically dissipative material may provide a dissipative path from the coating to ground. The ability to discharge the charge is believed to improve particle performance and defect performance to the substrate. Additionally, the coating 200 and / or pad 108 may provide a dissipative path between the supported wafer and ground. Any remaining charge on the wafer supported by the end effector 102 may be discharged by a path through the pad 108 and / or coating 200.
[0037] The coated end effector body (and other coated chamber parts) may be fabricated with an electrically dissipative material dopant to achieve the dissipative properties described above. However, fabricating doped parts by bulk doping or slurry-based coating can be costly due to a variety of factors, including limited supply, manufacturing and yield issues, and long lead times. Furthermore, doped parts may result in brittle coatings with a wide range of electrical surface / sheet resistances that are widely distributed across the coating surface. This disclosure achieves the dissipative properties described above by depositing a coating 200 on the top surface of the end effector body (or another chamber part) by an atomic layer deposition (ALD) process, by a chemical vapor deposition (CVD) process, by a plasma enhanced atomic layer deposition (PEALD) process, by a metalorganic chemical vapor deposition (MOCVD) process, or by a molecular beam epitaxy (MBE) process, some of which are described in further detail with respect to FIGS. 4 and 5. These processes can be advantageous and cost-effective because bare chamber parts (e.g., bare end effector bodies) are more readily available, face fewer manufacturing and yield issues, have short lead times, etc. Furthermore, multiple chamber parts (e.g., multiple end effector bodies) may be coated simultaneously (e.g., by inserting multiple end effector bodies into an ALD, CVD, PEALD, MOCVD, or MBE deposition chamber). The resulting coatings can also be more uniform, more conformal, less porous, stronger, maintain their integrity longer, and have a narrower distribution of electrical surface / sheet resistance across the coating surface as compared to doped chamber parts (e.g., end effectors) or chamber parts (e.g., end effectors) coated by slurry-based coating processes.
[0038] The coating 200 may include an electrically dissipative material. In certain embodiments, the coating 200 may also include a corrosion resistant material, which may be a plasma corrosion and / or erosion resistant material.
[0039] In some embodiments, coating 200 may be a multi-layer coating in which at least one of the layers of the multi-layer coating is an electrically dissipative layer that includes one of the aforementioned electrically dissipative materials, and at least one other layer of the multi-layer coating is a plasma-resistant layer that includes a material that is resistant to plasma.
[0040] In some embodiments, the coating 200 is a multi-layer coating, and at least one layer of the multi-layer coating is made of aluminum oxide, yttrium oxide, zirconium oxide, Y 3 Al 5 O 12 , Y 2 O 3 -ZrO 2 solid solution, Y 4 Al 2 O 9 and Y 2 O 3 -ZrO 2 Compounds containing solid solutions, HfO 2 , HfAlO x , HfZrO x , HfYO x , Hf-doped Y 2 O 3 , zinc oxide, tantalum oxide, titanium oxide, erbium oxide, gadolinium oxide, lanthanum oxide, praseodymium oxide, neodymium oxide, promethium oxide, samarium oxide, europium oxide, terbium oxide, dysprosium oxide, holmium oxide, thulium oxide, ytterbium oxide, or lutetium oxide.
[0041] In some embodiments, the coating 200 is a multi-layer coating, and at least one layer of the multi-layer coating is 2 O 3 and Y 2 O 3 Base ceramic, Y 3 Al 5 O 12 (YAG), Al 2 O 3(Alumina), Y 4 Al 2 O 9 (YAM), YF 3 , SiC (silicon carbide), ErAlO 3 , GdAlO 3 , NdAlO 3 , YAlO 3 , Si 3 N 4 (silicon nitride), AlN (aluminum nitride), TiO 2 (Titania), ZrO 2 (zirconia), TiC (titanium carbide), ZrC (zirconium carbide), TiN (titanium nitride), Y 2 O 3 Stabilized ZrO 2 (YSZ), Er 2 O 3 and Er 2 O 3 Based ceramic, Gd 2 O 3 and Gd 2 O 3 Base ceramic, Er 3 Al 5 O 12 (EAG), Gd 3 Al 5 O 12 (GAG), Nd 2 O 3 and Nd 2 O 3 Base ceramic, Y 4 Al 2 O 9 and Y 2 O 3 -ZrO 2 Ceramic compounds containing solid solutions, Y 2 O 3 Ceramic compounds containing Er 2 O 3 , ZrO 2 , Gd 2 O 3 and SiO 2 , Hf-based oxides and solid solutions, Lanthanide-based oxides and solid solutions, or any combination of the above.
[0042] In some embodiments, coating 200 is a multi-layer coating, and at least one layer of the multi-layer coating includes a solid solution formed by any of the aforementioned ceramics. Coating 200 may also include layers that may be multiphase materials, including a solid solution of one or more of the aforementioned materials and one or more additional phases.
[0043] Y 2 O 3 -ZrO 2 Referring to a solid solution, the layer of coating 200 is composed of a 10 to 90 mole percent (mol%) Y 2 O 3 and ZrO with concentrations of 10 to 90 mol% 2 In some examples, Y 2 O 3 -ZrO 2 The solid solution is 10-20mol% Y 2 O 3 and 80-90 mol% ZrO 2 may contain 20 to 30 mol% of Y 2 O 3 and 70-80 mol% ZrO 2 may contain 30 to 40 mol% Y 2 O 3 and 60-70 mol% ZrO 2 and 40 to 50 mol% of Y 2 O 3 and 50-60 mol% ZrO 2 and 60 to 70 mol% of Y 2 O 3 and 30-40 mol% ZrO 2 and 70 to 80 mol% of Y 2 O 3 and 20-30 mol% ZrO 2 and 80 to 90 mol% of Y 2 O 3 and 10-20 mol% ZrO 2 and so on.
[0044] Y 4 Al2 O 9 and Y 2 O 3 -ZrO 2 With reference to the layer of coating 200 that includes a solid solution, in one embodiment, the ceramic compound has a molar ratio (mol%) of 62.93 Y 2 O 3 , 23.23mol% ZrO 2 and 13.94 mol% Al 2 O 3 In another embodiment, the ceramic compound comprises Y in the range of 50 to 75 mol %. 2 O 3 , ZrO in the range of 10-30 mol% 2 , and Al in the range of 10-30 mol% 2 O 3 In another embodiment, the coating 200 can include Y in the range of 40-100 mol %. 2 O 3 , ZrO in the range of 0.1 to 60 mol% 2 , and Al in the range of 0.1 to 10 mol% 2 O 3 In another embodiment, the layer of coating 200 may include Y in the range of 40-60 mol %. 2 O 3 , ZrO in the range of 35-50 mol% 2 , and Al in the range of 10-20 mol% 2 O 3 In another embodiment, the layer of coating 200 may include Y in the range of 40-50 mol %. 2 O 3 , ZrO in the range of 20-40mol% 2 , and Al in the range of 20-40 mol% 2 O 3 In another embodiment, the layer of coating 200 may include Y in the range of 80-90 mol %. 2 O 3 , ZrO in the range of 0.1 to 20 mol% 2 , and Al in the range of 10-20 mol% 2 O 3In another embodiment, the layer of coating 200 may include Y in the range of 60-80 mol %. 2 O 3 , ZrO in the range of 0.1 to 10 mol% 2 , and Al in the range of 20-40 mol% 2 O 3 In another embodiment, the layer of coating 200 may include Y in the range of 40-60 mol %. 2 O 3 , ZrO in the range of 0.1 to 20 mol% 2 , and Al in the range of 30-40 mol% 2 O 3 In other embodiments, other proportions may also be used for one or more layers of coating 200.
[0045] In one embodiment, the coating 200 is a multi-layer coating, with at least one layer being 2 O 3 , ZrO 2 , Er 2 O 3 , Gd 2 O 3 and SiO 2 In one embodiment, the layer of coating 200 comprises or consists of a ceramic compound including a combination of Y in the range of 40-45 mol %. 2 O 3 , ZrO in the range of 0 to 10 mol% 2 , Er in the range of 35-40 mol% 2 O 3 , Gd in the range of 5-10 mol% 2 O 3 , and SiO in the range of 5 to 15 mol%. 2 In a first example, the layer of coating 200 may include 40 mol % Y. 2 O 3 , 5mol% ZrO 2 , 35mol% Er 2 O 3 , 5mol% Gd 2 O 3and 15 mol% SiO 2 In a second example, the layer of coating 200 contains 45 mol % Y. 2 O 3 , 5mol% ZrO 2 , 35mol% Er 2 O 3 , 10mol% Gd 2 O 3 and 5 mol% SiO 2 In a third example, the layer of coating 200 includes 40 mol % Y. 2 O 3 , 5mol% ZrO 2 , 40mol% Er 2 O 3 , 7mol% Gd 2 O 3 and 8 mol% SiO 2 Includes.
[0046] Any of the above mentioned coating materials are ZrO 2 , Al 2 O 3 , SiO 2 , B 2 O 3 , Er 2 O 3 , Nd 2 O 3 , Nb 2 O 5 , CEO 2 , Sm 2 O 3 , Yb 2 O 3 or other oxides.
[0047] In some embodiments, as discussed above, the coating 200 may include a stack of alternating layers including a first material and layers including a second material. The layers including the first material may include a single metal or metal alloy. Exemplary metals or metal alloys that may be used for the layers including the first material may include metals or metal alloys whose oxides are typically used as ceramics in bulk. In some embodiments, the layers including the first material may include one or more of Al, Zr, Y-Zr, Mg-Al, Ca-Al, or Si. The layers including the second material may be resistivity modifiers, such as, but not limited to, one or more of a transition metal, rare earth, main group metal, semiconductor, or alloys thereof. In some embodiments, the layers including the second material may include one or more of Ti, Fe, Co, Cu, Ni, Mn, V, Y, Nb, In, Sn, Fe-Co, or La-Ta.
[0048] In some embodiments, the layer including the first material and the layer including the second material may independently be an oxide, hydroxide, nitride, carbide, or metallic (i.e., little or no oxygen or hydrogen or nitrogen or carbon). In one embodiment, the layer including the first material and the layer including the second material may both be in oxide, hydroxide, nitride, carbide, or metallic form. In another embodiment, the layer including the first material may have a different morphology than the layer including the second material. For example, the layer including the first material may be aluminum hydroxide (e.g., Al 2 O 2.99 H 0.01 ), and the layer comprising the second material may be metallic Ti, TiN, SiC, metallic Al, etc.
[0049] In some embodiments, the layer including the first material may have a first target thickness and the layer including the second material may have a second target thickness. The ratio of the first target thickness to the second target thickness may be in the range of about 50:1 to about 1:50, about 30:1 to about 1:30, about 20:1 to about 1:20, about 10:1 to about 1:10, about 10:1 to about 1:1, about 8:1 to about 1:1, about 5:1 to about 1:1, about 10:1 to about 2:1, about 8:1 to about 2:1, about 5:1 to about 2:1, or about 5:2 to about 1:1.
[0050] In one embodiment, the coating 200 can be alumina. In one embodiment, the coating 200 can be titania. In one embodiment, the coating 200 can be a combination of alumina and titania, such as an alternating alumina and titania stack. In one embodiment, the electrically dissipative material is a stack of alternating layers of alumina and titania, with the ratio of the thickness of each alumina layer to the thickness of each titania layer in the stack ranging from about 10:1 to about 1:10. For example, the thickness ratio can be from about 8:1 to about 1:1, from about 5:1 to about 1:1, from about 10:1 to about 2:1, from about 8:1 to about 2:1, from about 5:1 to about 2:1, or from about 5:2 to about 1:1. In one embodiment, the electrically dissipative material can be a stack of alumina and metallic titanium, or a stack of aluminum hydroxide and metallic titanium, or the like.
[0051] For example, FIG. 7A depicts an energy dispersive X-ray spectroscopy (EDS) line scan of a coating comprising a stack of alternating layers of alumina and titania, and FIG. 7B depicts a transmission electron microscope (TEM) image at a 50 nm scale of the coating depicted in FIG. 7A. In FIG. 7A, the atomic % of oxygen is depicted in graphical representation 730, the atomic % of aluminum is depicted in graphical representation 720, and the atomic % of titanium is depicted in graphical representation 710. FIG. 7A illustrates that the electrically dissipative coating comprises well-separated alternating stacks of alumina and titania, evidenced in part by the wavy graphical representations 710 and 720 in the 30 nm to 130 nm range. The electrically dissipative coating depicted in FIGS. 7A and 7B comprises well-separated layers, with each alumina (AlO x ) layers have a thickness of about 5 nm, and each titania (TiO y The SiO 2 SiO 2 layers have a thickness of about 2 nm. The ratio of the thickness of each alumina layer to the thickness of each titania layer can be evidenced by the atomic percentage of aluminum compared to the atomic percentage of titanium in the EDS line scan of FIG. 7A. The entire electrically dissipative coating has a thickness of about 100 nm. The electrically dissipative coating was deposited on the bulk alumina surface as evidenced in the EDS line scan of FIG. 7A in the range of 140 nm to 280 nm.
[0052] The coating 200 may be crystalline or amorphous and may be uniform and conformal, covering the chamber components (e.g., the end effector body) and any features thereon (such as the contact pads 102) with a substantially uniform thickness. In one embodiment, the coating 200 has conformal coverage of the underlying surface (including the coated surface features) coated with a uniform thickness that varies less than about ±20%, less than about ±10%, less than about ±5%, or less when comparing the thickness of the coating at one location to the thickness of the coating at another different location (or when evaluating the standard deviation obtained from multiple thicknesses evaluated at multiple locations). The TEM image in FIG. 7B of an electrically dissipative coating according to an embodiment illustrates a coating of uniform thickness across the depicted surface.
[0053] The coating 200 may also have a substantially uniform electrical surface / sheet resistance, or in other words, a narrow distribution of electrical surface / sheet resistance across the surface of the coating. In some embodiments, the coating 200 has a uniform electrical surface / sheet resistance with less than about ±35% variation in electrical surface / sheet resistance, less than about ±30%, less than about ±25%, less than about ±20%, less than about ±10% variation in electrical surface / sheet resistance, less than about ±5% variation in electrical surface / sheet resistance, or less than about ±10% variation in electrical surface / sheet resistance.
[0054] For example, Figures 9A and 9B depict images of the front and back, respectively, of an exemplary end effector coated with a coating according to one embodiment. The sheet resistance values measured at each of the identified locations are summarized in Table 1 below. TIFF0007662619000001.tif172170
[0055] For comparison, Figures 10A and 10B depict front and back images, respectively, of an exemplary bulk-doped ceramic end effector. The sheet resistance values measured at each of the identified locations are summarized in Table 2 below. TIFF0007662619000002.tif177170
[0056] The standard deviations in Tables 1 and 2 are indicative of the uniformity of the sheet resistance values at various locations on an end effector. The standard deviations in Table 2 indicate significant non-uniformity in sheet resistance across the surface of a bulk-doped ceramic end effector. In comparison, coating the end effector according to the embodiments described herein improves the uniformity of sheet resistance across the surface of the end effector. This can be evidenced by the small standard deviations in Table 1 and the narrow distribution of electrical surface / sheet resistance across the coated surface.
[0057] Because the deposition processes described herein (ALD, CVD, PEALD, MOCVD, MBE) are highly conformal processes, the coating 200 can have a roughness that matches the roughness of the underlying surface being coated. In certain embodiments, the coating 200 can have a surface roughness that is within about ±20% or less, about ±10% or less, or about ±5% or less compared to the surface roughness of the underlying surface being coated. The coatings described herein can be advantageous for parts having high aspect ratios (e.g., aspect ratios of about 3:1 to about 300:1, 20:1, 50:1, 100:1, 150:1, etc.), complex geometries, and three-dimensional structures, because they uniformly and conformally coat the surface of the part overall, including all intricate features thereon.
[0058] For example, according to one embodiment, a 50 nm thick alumina-titania (ratio of alumina layer thickness to titania layer thickness is 5 nm:2 nm, electrical surface / sheet resistance is about 1.6×10 7Surface micrographs (not shown) of samples coated with the nanolaminate (according to ASTM D-257 method) showed that the coating was conformal, thin, crack-free, and conformed to the surface roughness of the underlying alumina substrate.
[0059] This was further supported by scanning electron microscope (SEM) images (not shown) from the top of an undoped bare alumina substrate and an alumina substrate coated with nanolaminate. The roughness of the undoped bare alumina substrate was measured to be 51±13 microinches. The roughness of the nanolaminate coated alumina substrate was measured to be 49±6 microinches. The roughness measurements and the two SEM images showed that the coating according to the embodiments described herein, at 200 nm thick, retained the features and roughness of the underlying substrate. This data indicates that the mechanical properties and features of the underlying substrate were retained by the thin conformal coating described herein at the sub-micron scale.
[0060] The coating 200 may be very dense and have very low porosity compared to other deposition techniques (such as e-beam IAD or plasma spray). For example, the coating 200 may have a porosity of less than about 1.5%, less than about 1%, less than about 0.5%, or about 0% (i.e., non-porous). As used herein, the term "non-porous" means free of any holes, pinholes, voids, or cracks throughout the entire depth of the coating 200 as measured by transmission electron microscopy (TEM). In contrast, with conventional e-beam IAD or plasma spray techniques or doping or slurry-based coatings, the porosity may be 1-5%, and in some cases much higher. The TEM image in FIG. 7B of an electrically dissipative coating according to an embodiment illustrates the dense and low porosity nature of the coating.
[0061] The end effector body 102 (or other chamber components) may be coated with a coating 200 that includes a corrosion resistant material to withstand processing in a corrosive plasma. Non-limiting examples of corrosive processing gases include C, C-C, C-H ... 2 F 6 ,SCIENCE FICTION 6 , SiCl 4 , HBr, NF 3 , C.F. 4 , CHF 3 , C.H. 2 F 3 , F, Cl 2 , CCl 4 , BCl 3 and SiF 4 Halogen-containing gases such as O 2 or N 2 Other gases include O.
[0062] The resistance of the coating 200 to plasma can be measured by the "etch rate" (ER), which may have units of angstroms per minute (Å / min), throughout the duration of operation of the coated part and exposure to the plasma. Plasma resistance may also be measured by erosion rate, which has units of nanometers per radio frequency hour (nm / RFHr), where 1 RFHr represents 1 hour of treatment at the plasma treatment conditions. Measurements can be taken after various treatment times. For example, measurements can be taken before treatment, after 50 treatment hours, after 150 treatment hours, after 200 treatment hours, etc. For halogen plasmas, erosion rates below about 100 nm / RFHr are typical for erosion resistant coatings. Variations in the composition of the coating 200 deposited on the end effector body (or other chamber parts) may result in multiple different plasma resistance or erosion rate values. Additionally, a single compositionally erosion resistant coating 200 exposed to various plasmas may have multiple different plasma resistance or erosion rate values. For example, the coating 200 may have a first plasma resistance or erosion rate for a first type of plasma and a second plasma resistance or erosion rate for a second type of plasma.
[0063] The electrical surface / sheet resistance of coating 200 is approximately 1×10, as measured using a surface / sheet resistance measurement system (such as a Prostat PRS-801 with Probe PRF-912) according to ASTM D-257 method. 4 Ω / sq.~approx. 1×10 12 Ω / sq., approximately 1×10 4 Ω / sq.~approx. 1×10 11 Ω / sq., approximately 1×10 5 Ω / sq.~approx. 1×10 11 Ω / sq., approximately 1×10 4 Ω / sq.~approx. 1×10 10 Ω / sq., approximately 1×10 4 Ω / sq.~approx. 1×10 9 Ω / sq., approximately 1×10 4 Ω / sq.~approx. 1×10 8 Ω / sq., approximately 1×10 4 Ω / sq.~approx. 1×10 7 Ω / sq., approximately 1×10 4 Ω / sq.~approx. 1×10 6 Ω / sq., approximately 1×10 4 Ω / sq.~approx. 1×10 5 Ω / sq., approximately 1×10 5 Ω / sq.~approx. 1×10 10 Ω / sq., approximately 1×10 5 Ω / sq.~approx. 1×10 9 Ω / sq., approximately 1×10 5 Ω / sq.~approx. 1×10 8 Ω / sq., approximately 1×10 5 Ω / sq.~approx. 1×10 7 Ω / sq., approximately 1×10 5 Ω / sq.~approx. 1×10 6 Ω / sq., approximately 1×10 6 Ω / sq.~approx. 1×10 11 Ω / sq., approximately 1×10 6 Ω / sq.~approx. 1×10 10 Ω / sq., approximately 1×10 6 Ω / sq.~approx. 1×10 9 Ω / sq., approximately 1×10 6 Ω / sq.~approx. 1×10 8 Ω / sq., approximately 1×10 6 Ω / sq.~approx. 1×107 Ω / sq., approximately 1×10 7 Ω / sq.~approx. 1×10 11 Ω / sq., approximately 1×10 7 Ω / sq.~approx. 1×10 10 Ω / sq., approximately 1×10 7 Ω / sq.~approx. 1×10 9 Ω / sq., approximately 1×10 7 Ω / sq.~approx. 1×10 8 Ω / sq., approximately 1×10 10 Ω / sq.~approx. 1×10 12 Ω / sq., approximately 1×10 10 Ω / sq.~approx. 1×10 11 Ω / sq. range, or any other electrical surface / sheet resistance between these ranges.
[0064] In certain embodiments, the electrical surface / sheet resistance of coating 200 may remain unchanged after thermal cycling at temperatures ranging from about 150° C. to about 800° C., from about 200° C. to about 750° C., from about 300° C. to about 700° C., from about 400° C. to about 600° C., or at about 500° C. In certain embodiments, after thermal cycling, coating 200 may have an electrical surface / sheet resistance within about ±35%, within about ±30%, within about ±25%, within about ±20%, within about ±10%, or within about ±5% compared to the electrical surface / sheet resistance of coating 200 before thermal cycling.
[0065] In an embodiment in which coating 200 comprises a 100 nm thick nanolaminate coating of alumina and titania on silicon (the ratio of the thickness of each alumina layer to the thickness of each titania layer is about 5:2, and the coating was deposited using ALD at 200° C.), the electrical surface / sheet resistance of the as-deposited coating is about 9.53×10 6 After subjecting the coating to thermal cycling, the resistance of the coating was approximately 3.90×10 6Ω / sq. Thermal cycling was performed by exposing the coating to 400° C. in air five times, each with a duration of 1 hour. Specifically, the thermal cycling profile to which the coating was exposed was as follows: a) increasing the temperature from 30° C. to about 400° C. at a rate of 10° C. / min, b) holding the coating at 400° C. for a duration of about 1 hour, c) decreasing the temperature to 60° C., d) repeating the cycle from a) to c) four more times, e) finally decreasing the temperature to 30° C.
[0066] The coating 200 may be resistant to thermal shock. Resistance to thermal shock can be evaluated by comparing the number of cracks and electrical surface / sheet resistance of the coating as-deposited to the number of cracks and electrical surface / sheet resistance of a coating exposed to a thermal shock. The coating can be exposed to a thermal shock by exposing the coating to 200° C. on a hot plate for about 10 minutes, followed by immersion of the heated coating in cold water, followed by air drying. After the thermal shock, a coating that is resistant to thermal shock can have an electrical surface / sheet resistance within about ±35%, about ±30%, about ±25%, about ±20%, about ±10%, or about ±5% of the electrical surface / sheet resistance of the coating before the thermal shock. A coating that is resistant to thermal shock can be a coating that is crack-free before the thermal shock and crack-free after exposure to the thermal shock.
[0067] For example, a coating of nanolaminate having a thickness of 100 nm with AlO:TiO of 5 nm:3 nm (i.e., a ratio of each alumina layer thickness to each titania layer thickness of 5:3) was deposited on a quartz coupon without an intermediate buffer layer between the quartz coupon and the coating. The sheet resistance of this exemplary coating as-deposited was 5.7(±1.2)×E6Ω / square. After subjecting the coated coupon to a 200° C. shock test, the sheet resistance of the coating was 7.3(±1)×E6Ω / square. This data shows that the resistive performance of the illustrated coating was independent of the resistive performance of the underlying component (i.e., the substrate, which in this example was a quartz coupon). This data also shows that the coating maintained its electrical surface / sheet resistance after the thermal shock within at least ±35% of the electrical surface / sheet resistance of the coating before the thermal shock.
[0068] In an embodiment in which coating 200 comprises a 50 nm thick nanolaminate coating of alumina and titania (where the ratio of the thickness of each alumina layer to the thickness of each titania layer is about 5:2), the electrical surface / sheet resistance of the as-deposited coating is about 1.6×10 7 After the coating was subjected to a heat treatment at 200° C., the resistance of the coating was about 1.90×10 Ω / sq., measured according to the ASTM D-257 method. 8 It was Ω / sq.
[0069] Coating 200 may be vacuum resistant. Resistance to vacuum can be assessed by comparing the electrical sheet resistance of coating 200 outside of vacuum and inside of vacuum. In vacuum, a coating that is vacuum resistant may have an electrical sheet resistance within about ±35%, about ±30%, about ±25%, about ±20%, about ±10%, or about ±5% of the electrical sheet resistance of the preceding coating outside of vacuum. In an embodiment where coating 200 includes an alumina and titania nanolaminate coating (the ratio of the thickness of each alumina layer to the thickness of each titania layer is about 5:2, and the coating was deposited at 200° C.), the electrical sheet resistance of the coating in vacuum at 298 K (or 500 K) is within about ±20% of the electrical sheet resistance of the coating outside of vacuum at 298 K (or 500 K), as can be seen in FIG. 8.
[0070] Coating 200 is approximately 500kg / mm 2 ~Approx. 1000kg / mm 2 , approx. 600kg / mm 2 ~ approx. 900kg / mm 2 , or about 700 kg / mm 2 ~ approx. 800kg / mm 2 The coating 200 may have a Vickers hardness in the range of about 100 GPa to about 300 GPa, about 120 GPa to about 250 GPa, or about 150 GPa to about 200 GPa.
[0071] In an embodiment where the coating 200 comprises a nanolaminate coating of alumina and titania on silicon (the ratio of the thickness of each alumina layer to the thickness of each titania layer is 5:2, and the coating was deposited at 200° C.), the Vickers hardness value is about 791.88±50.55 kg / mm 2The hardness and indentation rate are about 168.74±7.42 GPa. The hardness and indentation rate can be measured using a nano hardness tester at a temperature of about 21-23°C, using maximum forces of about 0.5 mN, 1.0 mN, 2.0 mN, and 5.0 mN, a load application time of about 15 seconds, an unloading time of about 15 seconds, and a rest time of about 10 seconds, with a Poisson's ratio of about 0.2 and an indenter ID of Berkovich Diamond.
[0072] In comparison, the Vickers hardness value of 100 nm alumina deposited by ALD at 120 °C is approximately 510 kg / mm 2 and the Vickers hardness value of 100 nm titania deposited by ALD at 120°C is approximately 127 kg / mm 2 For α-alumina minerals, the Vickers hardness is about 1365 kg / mm 2 The elastic modulus is about 370 GPa. For anatase titania minerals, the Vickers hardness is about 980 kg / mm 2 and the elastic modulus is approximately 230-290 GPa.
[0073] Coating 200 may have a compositional purity of about 90% to about 100%, about 95% to about 99.9%, about 97% to about 99.8%, about 99% to about 99.7%, or about 99.5% as measured by X-ray photoelectron spectroscopy.
[0074] Suitable thicknesses for coating 200 may range from about 1 nm to 1000 nm. In embodiments, coating may have a maximum thickness of about 750 nm, a maximum thickness of about 500 nm, a maximum thickness of about 400 nm, a maximum thickness of about 300 nm, a maximum thickness of about 250 nm, a maximum thickness of about 200 nm, a maximum thickness of about 150 nm, a maximum thickness of about 100 nm, a maximum thickness of 50 nm, a maximum thickness of 30 nm, a maximum thickness of 20 nm, or another maximum thickness. In embodiments, coating 200 may have a minimum thickness of 5 nm, a minimum thickness of 10 nm, a minimum thickness of 20 nm, a minimum thickness of 25 nm, a minimum thickness of 35 nm, a minimum thickness of 50 nm, a minimum thickness of 100 nm, a minimum thickness of 150 nm, or another minimum thickness.
[0075] Referring back to FIG. 1 , the end effector 100 may include three contact pads 108. However, other embodiments may include other numbers of contact pads 108. The contact pads 108 may be included in the end effector body to minimize sliding of the substrate on the end effector body during transfer. To reduce substrate sliding, certain end effectors include integrally machined contact pads. The integrally machined contact pads may have dome-shaped contact surfaces with surface characteristics that contact and support the substrate and further reduce the tendency to slide. Each integrally machined contact pad may have a machined contact surface with a particular dome-shaped profile and surface roughness that may reduce the likelihood of substrate sliding on that contact pad. In some cases, wear of the integrally machined end effector contact pads and their contamination with silicon particles / dust may increase the tendency of the substrate to slide on the contact pads and therefore limit the useful life of the end effector. To prevent the substrate from sliding, the entire end effector may be replaced periodically. In some embodiments, the coating 200 covers the contact pads 180. In some embodiments, the contact pads 180 are constructed from an electrically dissipative material.
[0076] In certain embodiments of the present disclosure, replaceable contact pads are provided that can be quickly replaced and replaced as they wear out. Thus, the overall cost of continuing to provide a low-sliding end effector can be dramatically reduced. An exemplary replaceable contact pad that can be disposed on the end effector body 102 is shown in FIG.
[0077] As depicted in FIG. 3, the bottom surface 102B of the end effector body 102 may include a recess 214 formed therein. The recess 214 may be circular and may extend into the end effector body 102 from the bottom surface 102B to a depth HR. An aperture 215 may be formed in the end effector body 102 and may extend between the top surface 102T and the recess 214. The recess 214 may have, for example, a recess diameter DR of about 5 mm to about 10 mm, and a recess height HR of about 1.1 mm to about 2.0 mm. The aperture 215 may have, for example, an aperture DA diameter of about 2.8 mm to about 4.8 mm, and an aperture height HA of about 0.85 mm to about 1.1 mm. Other diameters and heights and depths may be used. Each may be larger for use with a 450 mm diameter substrate.
[0078] The contact pad 108 may include a contact pad head 208H having a contact surface 210 that may be configured to contact the substrate 101. The contact surface 210 may include a dome-like shape. The contact surface 210 may have a surface roughness of Ra about 45 μin to Ra about 65 μin, as measured using a surface gauge (such as a Surfcorder SE-2300 instrument conforming to JIS standards). The contact pad head 208H may have a contact pad height HP of, for example, about 1.0 mm to about 2.0 mm. The contact pad head 208H may have a contact pad diameter DP of, for example, 6.0 mm to 12.0 mm. Other suitable contact surface dimensions, geometries, radii, and surface roughnesses may be used.
[0079] The contact pad 108 may further include a shaft 212 coupled to the contact pad head 208H, and the shaft 212 may be received within the aperture 215. The contact pad head 208H and the shaft 212 may be integrally formed as one piece. The shaft 212 may further extend a distance from the underside 213 of the contact pad head 208H into the recess 214. The shaft 212 may include a shaft indent 216 formed therein. The shaft 212 may not extend below the bottom surface 102B of the end effector body 102 so as not to interfere with the placement of the substrate. The shaft indent 216 may be provided in the form of a groove and may be formed in the shaft 212 at a location between the underside 213 of the contact pad head 208H and the shaft end 212E of the shaft 212.
[0080] The axial indent 216 may include a surface contour having an arcuate bottom. The circular fastening member 218 may be received about the axial 212 and may seat within the axial indent 216 to secure the contact pad 108 to the end effector body 102. As the circular fastening member 218 seats within the axial indent 216, the circular fastening member 218 contacts the seating surface 214S of the recess 214 and also at least a portion of the axial indent 216. In the depicted embodiment, the circular fastening member 218 includes an O-ring that is pressed against the seating surface 214S in an as-installed state. The O-rings may be made from elastomeric materials such as perfluoroelastomers available as KALREZ® from DUPONT PERFORMANCE ELASTOMERS, copolymers of hexafluoropropylene (HFP) and vinylidene fluoride (VDF or VF2) available as VITON® from The Chemours Company, and other suitable high temperature elastomers. Elastomeric O-rings can be used up to about 316°C.
[0081] Replacement contact pad 108 arrangements other than those shown may be used. For example, replacement contact pads configured for use at elevated temperatures, from about 250° C. to about 650° C., or greater than about 320° C., may be used. In alternative embodiments, the axial indents 216 may vary (e.g., in shape, and / or size, and / or location), the securing members 218 may vary (e.g., in shape, and / or size, and / or location, and / or material of construction), any of the dimensions of any portion of the contact pad may vary, the material of construction of the contact pad may vary, etc.
[0082] In certain embodiments, the contact pads 108 may be made of, include, or consist of any of the materials of construction listed above for the end effector body. For example, in some embodiments, the contact pads 108 may include glass, quartz, ceramic, or a conductive material (such as a metallic material). Exemplary ceramics may include bulk alumina, alumina-SiC composite, SiC, silicon nitride, boron nitride, and boron. Exemplary conductive materials may include stainless steel, aluminum, nickel, copper, chromium, cobalt, molybdenum, ruthenium, tungsten, platinum, or other suitable metals or alloys (e.g., aluminum alloy Al6061).
[0083] The coating described above with respect to FIG. 2 may be deposited on the top surface of an end effector body (such as end effector body 102) and on the contact surfaces of contact pad heads (such as 208H) of contact pads deposited on the end effector body.
[0084] 4 depicts one embodiment of a deposition process by an ALD technique to deposit a coating on an article, such as a chamber part (e.g., an end effector body, with or without contact pads). One or more chamber parts (e.g., one or more end effectors) to be coated with any of the coatings described herein can be placed in a controlled temperature-pressure deposition chamber prior to the initiation of a selected deposition process, such as ALD, CVD, PEALD, MOCVD, MBE, etc.
[0085] There are various types of ALD processes, and the particular type can be chosen based on several factors, such as the surface to be coated, the coating material, and the chemical interaction of the surface with the coating material. The general principle of the various ALD processes involves growing a thin film layer by repeatedly exposing the surface to be coated to pulses of gaseous chemical precursors that chemically react with the surface in a self-limiting manner, one at a time.
[0086] FIG. 4 illustrates an article 110 having a surface. The article 110 can represent a chamber component (such as an end effector body similar to the end effector body 102 depicted in FIG. 1). In ALD, either the adsorption of a precursor onto a surface or the reaction of the adsorbed precursor with a reactant may be referred to as a "half-reaction." During the first half-reaction, a precursor 160 comprising a first material (such as a metal-containing precursor) is injected / pulsed onto the surface of the article 110 for a period of time sufficient to fully adsorb the precursor onto the surface. The adsorption is self-limiting as the precursor adsorbs onto a finite number of available sites on the surface, forming a uniform, conformal, and continuous adsorbed layer 114 on the surface. Any site that has already adsorbed a precursor becomes unavailable for further adsorption with the same precursor unless and / or until the adsorbed site is subjected to a process that forms new available sites onto the surface in a uniform, conformal, and continuous coating. Exemplary treatments may be plasma treatments, treatments by exposing the adsorbed layer to radicals, or the introduction of different precursors capable of reacting with the last layer adsorbed on the surface.
[0087] In some embodiments, two or more precursors are injected / pulsed together, either simultaneously or sequentially, and adsorbed on the surface of the article. Excess precursor is pumped / purged away by an inert gas. A first reactant 165 (e.g., an oxygen-containing oxidation / hydroxylation reactant, a nitrogen-containing reactant, a carbon-containing reactant, etc.) is then injected / pulsed and reacts with the adsorbed layer 114 to form a layer 116 comprising a first material (e.g., a first metal oxide layer, or a multi-metal oxide layer). The layer 116 comprising a first material can be uniform, continuous, conformal, and have low porosity. The layer 116 can have a thickness of less than one atomic layer to a few atoms after one ALD deposition cycle in some embodiments.
[0088] Multiple full ALD deposition cycles can be implemented to deposit thicker layer 116, with each full cycle (e.g., including introducing precursor 160, flushing / purging, introducing reactant 165, and flushing / purging again) adding an additional few atoms to a few atoms of thickness. As shown, up to n full cycles can be performed to grow layer 116 until the first target thickness is achieved, where n is an integer value greater than 1. In embodiments, layer 116 can have a first target thickness of about 5 Angstroms to about 100 Angstroms, about 10 Angstroms to about 80 Angstroms, or about 20 Angstroms to about 50 Angstroms. In some embodiments, the first target thickness may be in the range of about 1 nm to about 1000 nm, about 20 nm to about 500 nm, about 20 nm to about 400 nm, about 20 nm to about 300 nm, about 20 nm to about 200 nm, about 20 nm to about 100 nm, about 50 nm to about 100 nm, or about 20 nm to about 50 nm.
[0089] The article 110 having the layer 116 including the first material may then be introduced to an additional precursor, such as a precursor including a second material (e.g., a second metal-containing precursor) 170, for a second duration to form a third half-reaction and / or until a second adsorbed layer 118 is formed. The article 110 may then be introduced to a second reactant 175 to react with the adsorbed layer 118 to form a fourth half-reaction and / or to grow a layer 120 including the second material. The layer 120 may be uniform, continuous, conformal, and may have low porosity. The layer 120 may have a thickness of less than one atom to a few atoms (e.g., 2-3 atoms) after one complete cycle (e.g., including introducing the precursor 170, flushing / purging, introducing the reactant 175, and flushing / purging again). Multiple cycles may be implemented to deposit a thicker layer 120, with each cycle adding an additional few atoms to a few atoms of thickness. As shown, the complete cycle is repeated m times such that layer 120 has a second target thickness, where m is an integer value greater than 1. In embodiments, layer 120 may have a second target thickness of about 1 Angstrom to about 50 Angstroms, about 5 Angstroms to about 30 Angstroms, or about 10 Angstroms to about 20 Angstroms. In some embodiments, the second target thickness may range from about 1 nm to about 1000 nm, about 20 nm to about 500 nm, about 20 nm to about 400 nm, about 20 nm to about 300 nm, about 20 nm to about 200 nm, about 20 nm to about 100 nm, about 50 nm to about 100 nm, or about 20 nm to about 50 nm.
[0090] A complete ALD deposition cycle may be repeated z times until the total target thickness for the coating is achieved. The number of cycles z may be expressed by a fraction or integer having a value greater than 1 (e.g., 2 to 50, 5 to 30, 7 to 17, and any other number or range of numbers within these ranges). The total target thickness may range from about 1 nm to about 1000 nm, about 20 nm to about 500 nm, about 20 nm to about 400 nm, about 20 nm to about 300 nm, about 20 nm to about 200 nm, about 20 nm to about 100 nm, about 50 nm to about 100 nm, or about 20 nm to about 50 nm. The final coating may include a stack of alternating layers 116 including the first material and layers 120 including the second material.
[0091] The processes described herein above for forming a stack of alternating layers may also be referred to herein as sequential deposition. Other ALD sequences, such as co-deposition or co-dosing, may also be used herein (e.g., co-injecting multiple metal-containing precursors or sequentially injecting multiple metal-containing precursors prior to introducing reactants into the ALD deposition chamber).
[0092] After the stack of alternating layers is formed, an annealing process may be performed to diffuse the alternating layers of different materials into one another to form, in some embodiments, a composite coating having a single crystalline / amorphous phase or multiple crystalline / amorphous phases (e.g., composite oxides, composite hydroxides, composite nitrides, composite carbides, etc.). After the annealing process, the stack of alternating layers may become a single interdiffused coating layer (not shown in FIG. 4). For example, if the layers of the stack are Y 2 O 3 , Al 2 O 3 , and ZrO 2 In the case where 4 Al 2 O 9 and Y 2 O 3 -ZrO 2It may be a ceramic compound including a solid solution.
[0093] The ratio of n cycles (for depositing layer 116 including a first material) to m cycles (for depositing layer 120 including a second material) may be designated as n:m. n:m may correspond to the ratio of the first target thickness of each layer 116 to the second target thickness of each layer 120. n:m may also correspond to the composition ratio of the first material to the second material in coating 200.
[0094] In one embodiment, the coating 200 may be deposited on the top surface 102T of the end effector body (or on the top surface of other chamber components) using an ALD process as described in FIG. 4. The coating 200 may include an electrically dissipative material that is a stack (which may also be referred to herein as a nanolaminate) of alternating nanolayers 116 and 120. The ratio of the thickness of each nanolayer 116 to the thickness of each nanolayer 120 in the stack may range from about 50:1 to about 1:50, about 30:1 to about 1:30, about 20:1 to about 1:20, about 10:1 to about 1:10, about 10:1 to about 1:1, about 8:1 to about 1:1, about 5:1 to about 1:1, about 10:1 to about 2:1, about 8:1 to about 2:1, about 5:1 to about 2:1, or about 5:2 to about 1:1.
[0095] The first target thickness of the layer including the first material and the second target thickness of the layer including the second material may be different from one deposition cycle to another. For example, one layer of the layer including the first material may be 5 nm thick and another layer of the layer including the first material may be 7 nm thick. Similarly, one layer of the layer including the second material may be 2 nm thick and another layer of the layer including the second material may be 3 nm thick.
[0096] The deposition process temperature may correspond to the reactant composition in the coating 200. In other words, the deposition process temperature may determine the amount of oxygen, hydrogen, nitrogen, carbon, etc. in the coating 200. ALD processes may be performed at various temperatures depending on the type of process. The optimal temperature range for a particular ALD process is referred to as the "ALD temperature window." Temperatures below the ALD temperature window may result in poor growth rates and non-ALD type deposition. Temperatures above the ALD temperature window may result in reactions being displaced by chemical vapor deposition (CVD) mechanisms. The ALD temperature window may range from about 80°C to about 500°C, from about 100°C to about 400°C. In some embodiments, the ALD temperature window is between about 100 and 300°C, or is about 200°C.
[0097] The electrostatic dissipation of a chamber part (such as an end effector body) coated with coating 200 can be a function of the electrical surface resistance (or sheet resistance) of coating 200. The electrical surface / sheet resistance of coating 200 can be a function of the composition of the coating (e.g., n:m ratio and reactant composition / ingredients) and the thickness of the coating (determined by the number of complete ALD cycles, i.e., z value). For example, a 50 nm thick alumina-titania nanolaminate with an alumina layer thickness to titania layer thickness ratio of 5 nm:2 nm, all measured according to the ASTM D-257 method, has an electrostatic dissipation of approximately 1.6×10 7 A 100 nm thick alumina-titania nanolaminate with an electrical sheet resistance of 1.0 Ω / sq. and a ratio of alumina layer thickness to titania layer thickness of 5 nm:2 nm has a thermal conductivity of approximately 9.4 × 10 6 A 100 nm thick alumina-titania nanolaminate with an electrical surface / sheet resistance of Ω / sq. and a ratio of alumina layer thickness to titania layer thickness of 5 nm:1 nm has a surface / sheet resistance of approximately 7.5×10 7 The film had an electrical sheet resistance of 1.0 Ω / sq.
[0098] As can be understood from the ALD processes described hereinabove, the coating 200 can be formed using an atomically precise, layer-by-layer approach to create a nanolaminate with a composition and thickness that can be controlled in the sub-nanometer range.
[0099] In one embodiment, layer 116 may be alumina and layer 120 may be titania. Exemplary aluminum-containing precursors that may be used to deposit the alumina layer include, but are not limited to, trimethylaluminum (TMA), diethylaluminum ethoxide, tris(ethylmethylamido)aluminum, aluminum sec-butoxide, aluminum tribromide, aluminum trichloride, triethylaluminum (TEA), triisobutylaluminum, trimethylaluminum, or tris(diethylamido)aluminum.
[0100] Exemplary titanium-containing precursors that may be used to deposit the titania layer include, but are not limited to, tetrakis(dimethylamido)titanium, tetrakis(ethylmethylamido)titanium, titanium tetrachloride, titanium ethoxide, titanium isopropoxide, methylcyclopentadienyl titanium isopropoxide, titanium dimethylaminoethoxide isopropoxide variants, tris(dimethylamido)ethylcyclopentadienyl titanium, cycloheptatrienylcyclopentadienyl titanium, tris(methoxy)cyclopentadienyl titanium.
[0101] Depending on the composition of the coating 200, other metal-containing precursors may be used.
[0102] Yttrium-based coatings may be deposited by ALD using yttrium-containing precursors such as, but not limited to, tris(N,N-bis(trimethylsilyl)amido)yttrium(III), yttrium(III) butoxide, tris(cyclopentadienyl)yttrium(III), and Y(thd)3 (thd=2,2,6,6-tetramethyl-3,5-heptanedionate).
[0103] Zirconium-based coatings may be deposited by ALD using zirconium-containing precursors such as, but not limited to, zirconium(IV) bromide, zirconium(IV) chloride, zirconium(IV) tert-butoxide, tetrakis(diethylamido)zirconium(IV), tetrakis(dimethylamido)zirconium(IV), or tetrakis(ethylmethylamido)zirconium(IV).
[0104] Hafnium based coatings include, but are not limited to, HfCl 4 It may be deposited by ALD using hafnium-containing precursors such as TEMAHf, TDMAHf, HfCp variants, and ZrCp variants.
[0105] Erbium-based coatings include, but are not limited to, tris-methylcyclopentadienyl erbium(III) (Er(MeCp) 3 ), erbium borane amide (Er(BA) 3 ), Er(TMHD) 3 It may also be deposited by ALD using erbium-containing precursors such as erbium(III) tris(2,2,6,6-tetramethyl-3,5-heptanedionate), and tris(butylcyclopentadienyl)erbium(III).
[0106] Exemplary oxidizing reactants that can be used in ALD processes include, but are not limited to, oxygen, oxygen radicals, water, ozone, alcohol reactants, etc. Other exemplary reactants that can be used in ALD processes to form an electrically dissipative layer stack include, but are not limited to, reducing agents (H 2 , H 2 Plasma, organometallic reagents such as aluminum hydride derivatives, silanes), nitriding agents (ammonia, amines, N 2 ), carburizing agents (alkanes), etc.
[0107] In some embodiments, the coating 200 may be deposited on a surface of a chamber part (e.g., an end effector body, with or without contact pads) by a CVD process. An exemplary CVD system is illustrated in FIG. 5. The system includes a chemical vapor precursor delivery system 505 and a CVD reactor 510. The role of the vapor precursor delivery system 505 is to generate a vapor precursor 520 from a starting material 515, which may be in solid, liquid, or gas form. The vapor may then be transported into the CVD reactor 510 and deposited as a coating 525 and / or 545 on a surface of an article 530 (such as the top surface 102T of the end effector body), which may be positioned in an article holder 535.
[0108] The coating depicted in Figure 5 includes a bilayer, layer 525 and layer 545. Although a bilayer is merely illustrated with respect to the CVD process, one of ordinary skill in the art will appreciate that multi-layer coatings (such as stacks of two or more alternating layers) are also contemplated herein with respect to the CVD process. Multi-layer coatings including stacks of alternating layers of alumina and titania deposited by CVD are contemplated herein in certain embodiments.
[0109] The CVD reactor 510 heats the article 530 to a deposition temperature using a heater 540. In some embodiments, the heater may heat the walls of the CVD reactor (also known as a "hot wall reactor"), which may transfer heat to the article. In other embodiments, the walls of the CVD reactor may be kept cool and only the article may be heated (also known as a "cold wall reactor"). It should be understood that the configuration of the CVD system should not be construed as limiting. A variety of equipment is available for the CVD system, and the equipment is selected to provide optimal processing conditions that can provide a coating having a uniform thickness, surface morphology, structure, and composition.
[0110] Various CVD techniques include the following phases: (1) generating active gaseous reactant species (also known as "precursors") from starting materials; (2) delivering the precursors to a reaction chamber (also called a "reactor"); (3) absorbing the precursors onto a heated article; (4) engaging in a chemical reaction between the precursors and the article at the gas-solid boundary to form deposits and gaseous by-products; and (5) removing the gaseous by-products and unreacted gaseous precursors from the reaction chamber.
[0111] Suitable CVD precursors may be stable at room temperature, may have a low vaporization temperature, produce a stable vapor at low temperature, have a suitable deposition rate (slow deposition rate for thin film coatings, fast deposition rate for thick film coatings), relatively low toxicity, be cost-effective, and relatively pure. For some CVD reactions, such as pyrolysis reactions (also known as "pyrolysis") or disproportionation reactions, the chemical precursor alone may be sufficient to complete the deposition.
[0112] CVD has many advantages, including its ability to deposit dense, pure coatings and its ability to create uniform films with good reproducibility and adhesion at reasonably fast deposition rates. In embodiments, layers deposited using CVD may have less than 1% porosity, less than 0.1% porosity, or be non-porous (e.g., 0% porosity). Thus, it can be used to uniformly coat parts with complex shapes and deposit conformal films with good conformal coverage (e.g., substantially uniform thickness). CVD can also be utilized to deposit films made of multiple components, for example, by feeding multiple chemical precursors into a mixing chamber at a predetermined rate and then feeding the mixture into a CVD reactor system.
[0113] The CVD processes contemplated herein may utilize some of the precursors listed above for the ALD processes contemplated herein.
[0114] In certain embodiments, it may be preferable to deposit coating 200 using an ALD process rather than a CVD process.
[0115] FIG. 6 illustrates an exemplary embodiment of an electronic device processing tool 600 including a transfer robot 650 having an end effector 100 supporting a substrate 101 (shown in dotted lines for illustrative purposes), the substrate 101 being supported on a (integral or replaceable) contact pad. The end effector 100 (with or without a contact pad deposited thereon) may be coated with an electrically dissipative material using an ALD, CVD, PEALD, or MBE process as described herein. The electronic device processing tool 600 may include multiple processing chambers 655 (shown in dotted lines) coupled to a transfer chamber 648. The transfer chamber 648 may house a transfer chamber (TC) robot 650. The TC robot 650 may have a first arm 651, a second arm 652, and a third arm 653 (e.g., a robot wrist). The end effector 100 is coupled to the third arm 653 via a mounting plate 654 or the like. The end effector 100 is capable of contacting and supporting a substrate 101 thereon (eg, a semiconductor wafer, a glass plate, etc.).
[0116] The transfer chamber 648 of the processing tool 600 may be connected to a factory interface 662 via one or more load lock chambers 656. The factory interface 662 may house a factory interface (FI) robot 661. The FI robot 661 may include an end effector (not shown, but substantially identical to the end effector 100) that may have replaceable contact pads 108 as described herein and may be coated with an electrically dissipative material using an ALD or CVD process as described herein.
[0117] The substrate carrier 664 may be removably connected to the front wall of the factory interface 662, and the substrates 101 therein may be moved between the substrate carrier 664 and one or more load lock chambers 656 by the FI robot 661.
[0118] The processing tool 100 may be coupled to a controller 665. The controller 665 may control the movement of the substrate 101 and its processing. The controller 665 may include, for example, a central processing unit (CPU), supporting circuits, and memory. In operation, the TC robot 650 operates under commands from the controller 665 and may, for example, move the substrate 101 between various processing chambers 655 and load lock chambers 656 or between different processing chambers 655.
[0119] As the manufacturing process progresses, the FI robot 661 and the TC robot 650 can operate simultaneously to move the substrate 101 between the substrate carrier 664 and the processing chamber 655. Various electronic device fabrication processes, such as semiconductor device manufacturing processes, such as oxidation, thin film deposition, etching, heat treatment, degassing, cooling, etc., can be performed in the processing chamber 655.
[0120] Although the TC chamber robot 650 is described as having an end effector coated with an electrically dissipative coating, the FI robot 661 may additionally or alternatively include an end effector having an electrically dissipative coating.
[0121] In a first embodiment, a coated chamber component includes a chamber component and a coating deposited on a surface of the chamber component, the coating including an electrically dissipative material, the electrically dissipative material providing a dissipative path from the coating to ground, the coating being uniform, conformal, and nonporous, the coating having a thickness in a range of about 10 nm to about 900 nm, and the coating having a surface area of about 1×10 5 Ω / sq.~approx. 1×10 11Coated chamber parts are described that include a coating having an electrical surface / sheet resistance in the ohm / sq. range.
[0122] In a second embodiment, a coated chamber part of the first embodiment is described, wherein the electrical surface / sheet resistance of the coating remains unchanged after being subjected to thermal cycling at temperatures in the range of about 300°C to about 700°C.
[0123] In a third embodiment, the coated chamber part of the first embodiment is described, wherein the coating has a thickness in the range of about 20 nm to about 900 nm.
[0124] In a fourth embodiment, the coated chamber part of the first embodiment is described, wherein the chamber part comprises a conductive material, a ceramic, a polymer, or quartz.
[0125] In a fifth embodiment, the coating has a resistance of about 500 kg / mm 2 ~Approx. 1000kg / mm 2 A first embodiment of a coated chamber component is described having a Vickers hardness in the range of 0.1 to 0.5.
[0126] In a sixth embodiment, a coated chamber part of the first embodiment is described, wherein the electrical surface / sheet resistance of the coating is uniform as evidenced by a variation in electrical surface / sheet resistance across the coating of less than about ±35%.
[0127] In a seventh embodiment, the coated chamber part of the first embodiment is described, wherein the electrically dissipative material comprises a stack of alternating layers comprising a first material and layers comprising a second material.
[0128] In an eighth embodiment, the coated chamber part of the seventh embodiment is described, wherein the layer comprising the first material comprises a metal or metal alloy comprising one or more of Al, Zr, Y-Zr, Mg-Al, Ca-Al, Si.
[0129] In a ninth embodiment, the coated chamber part of the seventh embodiment is described, wherein the layer comprising the second material comprises a transition metal, a rare earth, a main group metal, a semiconductor, or an alloy thereof.
[0130] In a tenth embodiment, the coated chamber part of the ninth embodiment is described, wherein the layer comprising the second material comprises one or more of Ti, Fe, Co, Cu, Ni, Mn, V, Y, Nb, In, Sn, Fe-Co, La-Ta.
[0131] In an eleventh embodiment, the coated chamber part of the seventh embodiment is described, wherein the ratio of the thickness of each layer comprising a first material to the thickness of each layer comprising a second material in the alternating stack is in the range of about 50:1 to about 1:50.
[0132] In a twelfth embodiment, the coated chamber part of the first embodiment is described, wherein the coating is resistant to corrosive plasma.
[0133] In a thirteenth embodiment, a method includes depositing a coating on a surface of a chamber component using an atomic layer deposition (ALD) process, a chemical vapor deposition (CVD) process, a plasma enhanced atomic layer deposition (PEALD) process, metalorganic chemical vapor deposition (MOCVD), or a molecular beam epitaxy (MBE) process, the coating including an electrically dissipative material, the electrically dissipative material providing a dissipative path from the coating to ground, the coating being uniform, conformal, and nonporous, the coating having a thickness in the range of about 10 nm to about 900 nm, and the coating having a surface area of about 1×10 5 Ω / sq.~approx. 1×10 11 A method is described that has electrical surface / sheet resistance in the Ω / sq. range.
[0134] In a fourteenth embodiment, depositing a coating using an ALD process includes injecting a precursor including a first material into a deposition chamber including a chamber part to adsorb the precursor including the first material on a surface of the chamber part to form a first half-reaction, injecting a first reactant into the deposition chamber to form a second half-reaction, repeating the injecting of the precursor including the first material and the injecting of the first reactant one or more times until a first target thickness of a layer including the first material of the coating is achieved, and injecting a precursor including the second material into the deposition chamber to form a second half-reaction. performing a deposition cycle including injecting a precursor comprising the second material into the deposition chamber to adsorb the precursor comprising the second material into the layer comprising the first material to form a third half-reaction; injecting a second reactant into the deposition chamber to form a fourth half-reaction; and repeating the injection of the precursor comprising the second material and the injection of the second reactant one or more times until a second target thickness of the layer comprising the second material of the coating is achieved; and repeating the deposition cycle one or more times until a thickness in the range of about 20 nm to about 500 nm is achieved. And A method of a thirteenth embodiment is described, which includes:
[0135] In a fifteenth embodiment, the method of the thirteenth embodiment is described, wherein the ratio of the first target thickness to the second target thickness ranges from about 50:1 to about 1:50.
[0136] In a sixteenth embodiment, the method of the thirteenth embodiment is described, wherein the first target thickness and the second target thickness may be different from one deposition cycle to another.
[0137] In a seventeenth embodiment, the coating has a molecular weight of about 1×10 5 Ω / sq.~approx. 1×10 11 A thirteenth embodiment method is described in which the coating has an electrical surface / sheet resistance in the range of Ω / sq., and the electrical surface / sheet resistance of the coating is uniform as evidenced by an electrical surface / sheet resistance variation across the coating of less than about ±35%.
[0138] In an eighteenth embodiment, the method of the thirteenth embodiment is described, wherein the layer comprising the first material comprises a metal or metal alloy comprising one or more of Al, Zr, Y-Zr, Mg-Al, Ca-Al, Si, and the layer comprising the second material comprises one or more of Ti, Fe, Co, Cu, Ni, Mn, V, Y, Nb, In, Sn, Fe-Co, La-Ta.
[0139] In a nineteenth embodiment, an electrically dissipative coating comprising an electrically dissipative material, wherein the coating is uniform, conformal, and non-porous, the coating has a thickness in the range of about 20 nm to about 500 nm, and the coating has a viscosity of about 1×10 5 Ω / sq.~approx. 1×10 11 Electrically dissipative coatings are described that have electrical surface / sheet resistances in the ohm / sq range.
[0140] In a twentieth embodiment, the electrically dissipative material comprises a stack of alternating layers comprising a first material and layers comprising a second material, the layers comprising the first material comprising a metal or metal alloy comprising one or more of Al, Zr, Y-Zr, Mg-Al, Ca-Al, Si, the layers comprising the second material comprising one or more of Ti, Fe, Co, Cu, Ni, Mn, V, Y, Nb, In, Sn, Fe-Co, La-Ta, and the coating has a thermal conductivity of about 500 kg / mm 2 ~Approx. 1000kg / mm 2 A nineteenth embodiment of an electrically dissipative coating is described having a Vickers hardness in the range of 0.1 to 0.5%, and the electrical surface / sheet resistance of the coating is uniform as evidenced by an electrical surface / sheet resistance variation across the coating of less than about ±35%.
[0141] In a twenty-first embodiment, an end effector for a robotic arm includes an end effector body and a coating deposited on a surface of the end effector body, the coating including an electrically dissipative material, the electrically dissipative material providing a dissipative path from the coating to ground, the coating being uniform, conformal, and non-porous, the coating having a thickness in the range of about 20 nm to about 500 nm, and the coating having a surface area of about 1×10 5 Ω / sq.~approx. 1×10 11 An end effector for a robotic arm is described that includes a coating having an electrical resistivity in the range of Ω / sq.
[0142] In a twenty-second embodiment, an end effector of the twenty-first embodiment is described, wherein the electrical resistance of the coating remains unchanged after being subjected to thermal cycling at temperatures ranging from about 300°C to about 700°C.
[0143] In a twenty-third embodiment, the end effector of the twenty-first embodiment is described, wherein the coating has a thickness in the range of about 20 nm to about 200 nm.
[0144] In a twenty-fourth embodiment, the end effector of the twenty-first embodiment is described, wherein the end effector body comprises a conductive material, ceramic, or quartz.
[0145] In a twenty-fifth embodiment, the end effector of the twenty-fourth embodiment is described, wherein the end effector body includes a conductive material that is a metal.
[0146] In a twenty-sixth embodiment, the end effector of the twenty-first embodiment is described, wherein the end effector body comprises a ceramic that is bulk alumina.
[0147] In a twenty-seventh embodiment, the end effector of the twenty-sixth embodiment is described, wherein the electrically dissipative material includes a conductive material, alumina, titania, or a combination thereof.
[0148] In a twenty-eighth embodiment, the end effector of the twenty-seventh embodiment is described, wherein the electrically dissipative material includes alternating stacks of alumina and titania.
[0149] In a twenty-ninth embodiment, the method of the twenty-eighth embodiment is described, wherein in the alternating alumina and titania stack, the ratio of the thickness of each alumina layer to the thickness of each titania layer ranges from about 10:1 to about 1:1.
[0150] In a thirtieth embodiment, the end effector of the twenty-fourth embodiment is described, wherein the end effector body comprises quartz and the coating is transparent.
[0151] In a thirty-first embodiment, the end effector of the twenty-first embodiment is described, wherein the coating is resistant to corrosive plasma.
[0152] In a thirty-second embodiment, the end effector of the twenty-first embodiment is described, further including a replaceable contact pad disposed on the end effector body, the replaceable contact pad including a contact pad head having a contact surface configured to contact a substrate, and a shaft coupled to the contact pad head and received within an aperture formed in the body of the end effector and extending into the recess.
[0153] In a thirty-third embodiment, the end effector of the thirty-second embodiment is described, wherein a coating is deposited on a surface of the end effector body and on a contact surface of the contact pad head.
[0154] In a thirty-fourth embodiment, a method includes depositing a coating on a surface of an end effector for a robotic arm using an atomic layer deposition (ALD) process or a chemical vapor deposition (CVD) process, the coating including an electrically dissipative material, the electrically dissipative material providing a dissipative path from the coating to ground, the coating being uniform, conformal, and nonporous, the coating having a thickness in the range of about 20 nm to about 500 nm, and the coating having a surface area of about 1×10 5 Ω / sq.~approx. 1×10 11 A method is described in which the dielectric constant of the dielectric constant layer is in the range of Ω / sq.
[0155] In a thirty-fifth embodiment, depositing a coating using an ALD process includes injecting a precursor including a first material into a deposition chamber including an end effector body to adsorb the precursor including the first material on a surface of the end effector body to form a first half-reaction, injecting a first reactant into the deposition chamber to form a second half-reaction, repeating the injecting of the precursor including the first material and the injecting of the first reactant one or more times until a first target thickness of a layer including the first material of the coating is achieved, and injecting a second reactant into the deposition chamber to form a second half-reaction. performing a deposition cycle including injecting a precursor including the second material into the deposition chamber to adsorb the precursor including the second material onto the layer including the first material to form a third half-reaction; injecting a second reactant into the deposition chamber to form a fourth half-reaction; and repeating the injection of the precursor including the second material and the injection of the second reactant one or more times until a second target thickness of the layer including the second material of the coating is achieved; and repeating the deposition cycle one or more times until a thickness in the range of about 20 nm to about 500 nm is achieved. And A method of a thirty-fourth embodiment is described that includes:
[0156] In a thirty-sixth embodiment, the method of the thirty-fifth embodiment is described, wherein the coating comprises a stack of alternating alumina and titania, the precursor comprising the first material is an aluminum-containing precursor comprising at least one of trimethylaluminum (TMA), diethylaluminum ethoxide, tris(ethylmethylamido)aluminum, aluminum sec-butoxide, aluminum tribromide, aluminum trichloride, triethylaluminum (TEA), triisobutylaluminum, trimethylaluminum, or tris(diethylamido)aluminum, the precursor comprising the second material is a titanium-containing precursor comprising at least one of tetrakis(dimethylamido)titanium, and the first reactant and the second reactant independently comprise at least one of water, ozone, alcohol, and oxygen.
[0157] In a thirty-seventh embodiment, the method of the thirty-sixth embodiment is described, wherein in the alternating alumina and titania stack, the ratio of the thickness of each alumina layer to the thickness of each titania layer ranges from about 10:1 to about 1:1.
[0158] In a thirty-eighth embodiment, a substrate processing system is described comprising: a chamber; a robot disposed in the chamber; and a robot arm connected to the robot, the robot arm comprising an end effector body; a replaceable contact pad disposed on the end effector body, the replaceable contact pad including a contact pad head having a contact surface configured to contact a substrate, and a shaft coupled to the contact pad head and received within an aperture formed in the body of the end effector and extending into a recess; and a coating deposited on a surface of the end effector body and a contact surface of the contact pad head, the coating including an electrically dissipative material, wherein the electrically dissipative material provides a dissipative path from the coating to ground, and the coating is uniform and conformal.
[0159] In a thirty-ninth embodiment, the end effector body comprises a conductive material, ceramic, or quartz, and the coating has a resistance of about 1×10 5 Ω / sq.~approx. 1×10 11 A thirty-eighth embodiment of a substrate processing system is described, wherein the coating has an electrical resistivity in the range of Ω / sq., the coating has a thickness in the range of about 20 nm to about 500 nm, and the coating is non-porous.
[0160] In a fortieth embodiment, the substrate processing system of the thirty-eighth embodiment is described, wherein the end effector body comprises bulk alumina and the electrically dissipative material comprises an alternating stack of alumina and titania.
[0161] In the preceding description, numerous specific details are set forth, such as specific materials, dimensions, process parameters, etc., to provide a thorough understanding of the present invention. Particular features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments. The phrases "example" or "exemplary" are used herein to mean serving as an example, instance, or illustration. Any aspect or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or advantageous over other aspects or designs. Rather, the use of the phrases "example" or "exemplary" is intended to simply present concepts in a representational manner. As used in this disclosure, the term "or" is intended to mean an inclusive "or" rather than an exclusive "or." That is, unless otherwise stated or clear from the context, "X includes A or B" is intended to mean any of the natural inclusive permutations. That is, if X includes A, if X includes B, or if X includes both A and B, then "X includes A or B" is satisfied under any of the aforementioned cases. References throughout this specification to "an embodiment," "a particular embodiment," or "one embodiment" mean that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment. Thus, the appearances of the phrases "an embodiment," "a particular embodiment," or "one embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment.
[0162] The invention has been described with reference to specific exemplary embodiments thereof. The specification and drawings are accordingly to be regarded in an illustrative rather than a restrictive sense. Various modifications of the invention in addition to those shown and described herein will become apparent to those skilled in the art and are intended to fall within the scope of the appended claims.
Claims
1. 1. A coated chamber part comprising: A chamber component; a coating deposited on a surface of the chamber component, the coating comprising an electrically dissipative material, the electrically dissipative material providing a dissipative path from the coating to ground, the coating being uniform, conformal and non-porous, the coating having a thickness in the range of 10 nm to 900 nm, and the coating having a surface area of 1×10 5 Ω / sq. ~ 1 x 10 11 A coating having an electrical surface / sheet resistance in the range of Ω / sq. Equipped with the coating comprises one or more layers comprising a first material and one or more layers comprising a second material; the layer comprising one or more first materials is in a metallic form comprising at least one of Al, Zr, Y-Zr, Mg-Al, and Ca-Al, or in a hydroxide form comprising at least one of Al, Zr, Y-Zr, Mg-Al, and Ca-Al; the layer comprising one or more second materials comprises a transition metal, a rare earth, a main group metal, a semiconductor, or an alloy thereof; Coated chamber parts.
2. 10. The coated chamber part of claim 1, wherein the electrical surface / sheet resistance of the coating remains unchanged after thermal cycling at temperatures ranging from 300.degree. C. to 700.degree.
3. The coated chamber part of claim 1, wherein the coating has a thickness in the range of 20 nm to 900 nm.
4. The coated chamber part of claim 1 , wherein the chamber part comprises a conductive material, a ceramic, a polymer, or quartz.
5. The coating has a resistance of 500 kg / mm 2 ~1000kg / mm 2 The coated chamber part of claim 1 having a Vickers hardness in the range of 0.1 to 0.
5.
6. 2. The coated chamber part of claim 1, wherein the electrical surface / sheet resistance of the coating is uniform as evidenced by an electrical surface / sheet resistance variation across the coating of less than ±35%.
7. 10. The coated chamber part of claim 1, wherein the electrically dissipative material comprises a stack of alternating layers comprising the one or more first materials and layers comprising the one or more second materials.
8. 2. The coated chamber part of claim 1, wherein the layer comprising the one or more second materials comprises one or more of Ti, Fe, Co, Cu, Ni, Mn, V, Y, Nb, In, Sn, Fe-Co, La-Ta.
9. 8. The coated chamber part of claim 7, wherein in the alternating stack, a ratio of a thickness of each layer comprising a first material to a thickness of each layer comprising a second material is in the range of 50:1 to 1:
50.
10. The coated chamber part of claim 1 , wherein the coating is resistant to corrosive plasma.
11. 1. A method comprising: depositing a coating on a surface of a chamber component using an atomic layer deposition (ALD) process, a chemical vapor deposition (CVD) process, a plasma enhanced atomic layer deposition (PEALD) process, a metal organic chemical vapor deposition (MOCVD) process, or a molecular beam epitaxy (MBE) process, the coating comprising an electrically dissipative material. Including, The electrically dissipative material provides a dissipative path from the coating to ground, the coating is uniform, conformal, and non-porous, the coating has a thickness in the range of 10 nm to 900 nm, and the coating has a dielectric constant greater than 1×10 5 Ω / sq. ~ 1 x 10 11 having an electrical surface / sheet resistance in the range of Ω / sq.; the coating comprises one or more layers comprising a first material and one or more layers comprising a second material; the layer comprising one or more first materials is in a metallic form comprising at least one of Al, Zr, Y-Zr, Mg-Al, and Ca-Al, or in a hydroxide form comprising at least one of Al, Zr, Y-Zr, Mg-Al, and Ca-Al; the layer comprising one or more second materials comprises a transition metal, a rare earth, a main group metal, a semiconductor, or an alloy thereof; method.
12. depositing the coating using the ALD process; injecting a precursor including a first material into a deposition chamber including the chamber part such that the precursor including the first material adsorbs on the surface of the chamber part to form a first half-reaction; injecting a first reactant into the deposition chamber to form a second half-reaction; repeating the injecting of a precursor comprising the first material and the injecting of the first reactant one or more times until a first target thickness of a layer comprising a first material of the coating is achieved; injecting a precursor including a second material into the deposition chamber to cause the precursor including the second material to adsorb onto the layer including the first material to form a third half-reaction; injecting a second reactant into the deposition chamber to form a fourth half-reaction; repeating the injecting of the precursor including the second material and the injecting of the second reactant one or more times until a second target thickness of the layer including the second material of the coating is achieved; performing a deposition cycle comprising: Repeating the deposition cycle one or more times until a thickness in the range of 20 nm to 500 nm is achieved. Including, The method of claim 11.
13. The method of claim 12, wherein a ratio of the first target thickness to the second target thickness ranges from 50:1 to 1:
50.
14. The method of claim 12 , wherein the first target thickness and the second target thickness may vary separately from one deposition cycle to another.
15. The coating is 1×10 5 Ω / sq. ~ 1 x 10 11 12. The method of claim 11, wherein the coating has an electrical surface / sheet resistance in the range of 1000 ohms / sq., and the electrical surface / sheet resistance of the coating is uniform as evidenced by an electrical surface / sheet resistance variation across the coating of less than ±35%.
16. 12. The method of claim 11, wherein the one or more layers comprising a second material comprise one or more of Ti, Fe, Co, Cu, Ni, Mn, V, Y, Nb, In, Sn, Fe-Co, La-Ta.
17. 1. An electrically dissipative coating comprising an electrically dissipative material, said coating being uniform, conformal, and non-porous, said coating having a thickness in the range of 20 nm to 500 nm, and said coating having a surface area of less than 1×10 5 Ω / sq. ~ 1 x 10 11 having an electrical surface / sheet resistance in the range of Ω / sq.; the electrically dissipative material provides a dissipative path from the coating to ground; the coating comprises one or more layers comprising a first material and one or more layers comprising a second material; the layer comprising one or more first materials is in a metallic form comprising at least one of Al, Zr, Y-Zr, Mg-Al, and Ca-Al, or in a hydroxide form comprising at least one of Al, Zr, Y-Zr, Mg-Al, and Ca-Al; the layer comprising one or more second materials comprises a transition metal, a rare earth, a main group metal, a semiconductor, or an alloy thereof; Electrically dissipative coating.
18. the electrically dissipative material comprises a stack of alternating layers comprising one or more first materials and one or more second materials; the layer(s) comprising a second material comprises one or more of Ti, Fe, Co, Cu, Ni, Mn, V, Y, Nb, In, Sn, Fe—Co, La—Ta; The coating has a resistance of 500 kg / mm 2 ~1000kg / mm 2 and has a Vickers hardness in the range of 20. The electrically dissipative coating of claim 17, wherein the electrical surface / sheet resistance of the coating is uniform as evidenced by an electrical surface / sheet resistance variation across the coating of less than ±35%.
Citation Information
Patent Citations
Robot blade for semiconductor processing device
JP2001053135A
Electrode structure, its manufacturing method, and imaging apparatus using electrode structure
JP2002292920A
How to form esd dissipative structural components
JP2006522223A
Non-line-of-sight deposition of erbium-based plasma-resistant ceramic coatings
JP2019522113A